The development of Spodoptera frugiperda (Lepidoptera: Noctuidae) on several varieties of maize - Novri Nelly; Hasmiandy Hamid; Eka Candra Lina; Yunisman Yunisman; Yaherwandi Yaherwandi; Yelsi Dwi Putri (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nelly N, Hamid H, Lina EC, Yunisman, Yaherwandi, Putri YD. 2023. The development of Spodoptera frugiperda (Lepidoptera: Noctuidae) on Several varieties of maize. Biodiversitas 24: 523-530. Fall armyworm (FAW) or Spodoptera frugiperda (Lepidoptera: Noctuidae) is an invasive pest in Indonesia that cause damage to maize (Zea mays). Farmers for animal feed mainly cultivate several varieties of maize in West Sumatra, Indonesia. Therefore, it is necessary to test the resistance of maize varieties to fall armyworms planted by farmers. Therefore, this research aims to determine the resistance of several observed maize varieties based on their effects on the developmental time of S. frugiperda. The study was arranged in a Completely Randomized Design (CRD) with five treatments and five replications. The treatments for larvae feed consisted of five maize varieties: Sukmaraga, NK-212, Pioneer 21, Bonanza F1, and Secada F1. The development length from egg to adult and life parameters in the second generation were observed. Results of the study showed that the larval and pupal stages of S. frugiperda in the Sukmaraga variety had a longer development duration than the other four varieties, with the larval stage at 20.38 days and pupae at 11.26 days. In addition, the lowest pupae weight was found in the Sukmaraga variety. The maize varieties affect the length of the larval stage and the weight of the pupae and eggs produced. Based on these results, it can be concluded that Sukmaraga is a variety causing a more prolonged larval stage and lower pupae weight than other varieties. Furthermore, the eggs produced by the second-generation female S. frugiperda adult are fewer than in different varieties.